2022
DOI: 10.1055/a-1845-5556
|View full text |Cite
|
Sign up to set email alerts
|

Development of new gastric endoscopic submucosal dissection training model: A reproducibility evaluation study

Abstract: Background Gastric endoscopic submucosal dissection (ESD) is a highly technical procedure mainly due to the distinctive shape of the stomach and diverse locations of lesions. We developed a new gastric ESD training model (G-Master) that could accurately recreate the location of the stomach and assessed the reproducibility of located lesions in the model. Methods The model comprises a simulated mucous membrane sheet made of konjac flour and a setting frame, which can simulate 11 locations of the stomach. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Applying our previously developed gastric ESD model 4 , we have developed a colorectal ESD training model using non-animal materials with KOTOBUKI Medical, Inc. (Saitama, Japan) to resolve these issues ( Fig. 1 ).…”
Section: Figmentioning
confidence: 99%
“…Applying our previously developed gastric ESD model 4 , we have developed a colorectal ESD training model using non-animal materials with KOTOBUKI Medical, Inc. (Saitama, Japan) to resolve these issues ( Fig. 1 ).…”
Section: Figmentioning
confidence: 99%
“…This is a major challenge for trainees. Therefore Mitsui et al evaluated the actual resection speed using G-Master and its ease of use, and reported that it is useful for gastric ESD training [24]. G-Master is used in our department for training prior to the conduct of gastric ESD procedures (Figure 2).…”
Section: Gastric Model Trainingmentioning
confidence: 99%
“…Therefore, the data may not have been obtained under the same conditions. Non‐animal ESD training models provide high reproducibility for both site and mucosa, 7–9 and data could have been collected under consistent conditions if such models were used. Further research is imperative to validate these findings in a clinical setting and must focus on the relationship between ESU analysis and clinical outcomes, including vital aspects such as tissue quality, adverse events, and recurrence rates.…”
mentioning
confidence: 99%